Migrant self-employment in Germany: on the risks, characteristics and determinants of precarious work - Stefan Berwing; Andrew Isaak; René Leicht (Self-Employment as Precarious Work: a European Perspective, 2019)
There has been a long-standing debate among scholars about the nature of migrant self-employment. A popular assumption of the narrative is that migrants are forced into low-wage sectors with poor working conditions due to a lack of resources and opportunities. Here, we study the extent and determinants of precarious self-employment in Germany as well as which types of fields and occupations are most affected by precarious working conditions. To answer these questions, we develop an indicator to operationalize precarious self-employment using the 2011 German Microcensus. Quantitative analysis reveals that while migrants are more frequently engaged in precarious self-employment in absolute terms, this difference does not reach statistical significance. However, we do find clear differences for the sector of economic activity and profession, which can be interpreted as endowment effects. Overall, our results tend towards debunking the assumption that equates migrant self-employment in Germany to precarious work.
Keywords: L26; E24; C33; C38; J15; J61; O15; F22; 330; Migrant Entrepreneurship; Self-Employment; Precarious Work; Germany; Panel Regression; Methods; Microcensus